Vascular Endothelial Growth Factor Secretion from Pituitary Folliculostellate Cells: Role of KATP Channels. (February 2014) - Budzik, J.; Omer, S.; Morris, J. F.; Christian, H. C.
<x xml:space="preserve">Abstract</x> Vascular endothelial growth factor (VEGF) is an endothelial cell mitogen responsible for physiological and pathological angiogenesis. Abnormal regulation of VEGF expression in anterior pituitary folliculostellate (FS) cells has been implicated in pituitary tumour progression. FS and endocrine cells express VEGF, which is considered to be secreted by the constitutive pathway. The present study investigated the mechanism of VEGF secretion in TtT/GF cells, a mouse FS cell line. TtT/GF cells were shown to express VEGF164, the most potent and bioavailable isoform of VEGF. Immunofluorescence and immunogold electron microscopy localised VEGF to the cytoplasm and small electron‐lucent vesicles. Pituitary adenylate cyclase‐activating polypeptide (PACAP), a well‐documented stimulant of VEGF secretion, caused a robust increase in VEGF secretion over 24 h. Glyburide, an ABCA1 and KATP channel blocker, also caused an increase in VEGF secretion when applied alone, and amplified the response to PACAP. Other ABCA1 transport blockers did not affect VEGF secretion. Exposure of TtT/GF cells to cycloheximide with PACAP or glyburide inhibited the increased secretion of VEGF, consistent with control of secretion at the transcription level. The SUR2B/Kir6.1 form of KATP channels was shown to be expressed by TtT/GF cells. Diazoxide, a KATP activator, inhibited PACAP‐ and PACAP + glyburide‐stimulated VEGF secretion but not that of glyburide alone. These data suggest that KATP channels are expressed by FS cells and play a significant role in the control of VEGF secretion, and also that activation of KATP channels inhibits the secretion of VEGF at the level of transcription.